APPLICATION OF THE METHOD OF LEAN PRODUCTION IN THE SERVICES SECTOR - A. Dmitriev; N. Barkova (Вестник университета)
The explanation of the essence of the method of lean production has been given and its goals. The question has been answered, why the method will work successfully not only in the production sector, but also in the service sector. It has been supposed, that the method of lean production can be actively implemented in the provision of warehousing services. A number of measures for the organization of warehousing on the basis of the principles of lean manufacturing has been offered, among which are allocated the following: improving the reliability of the collection of orders for shipment, optimization of warehouse space, reducing the number of warehouse operations and time to perform these operations.